PENGARUH TERPAAN BERITA TENTANG MASKAPAI LION AIR DI MEDIA INTERNET TERHADAP PERSEPSI RISIKO MAHASISWA PERANTAUAN ASAL PEKANBARU - Fitria, Nuzila; ", Suyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The internet has emerged as the new media that has become a very popular source of information. At the beginning of 2015, news on the problem of Lion Air became one of the popular topics on the internet. The spreading of news through the internet that can be categorized as fast may have given certain effects. Because of that, the media exposure of Lion Air on the internet may have influenced perceived risk regarding the airline. This research is based on McLuhanâ€™s idea on the Media Determination Theory that communication media can influence perception habits and thinking of individuals. The aim of this research is to know whether or not there is an effect of the news exposure on Lion Air on the internet towards the risk perception of students from Pekanbaru. The method used in this research is the explanatory quantitative approach. Data gathering technique uses questionnaires spread online through google form. Population of this research are students from Pekanbaru. Sampling technique used is accidental sampling towards 96 respondents. Results of this research uses descriptive analysis. To determine whether or not there is an influence of independent variables on the dependent variables, this research uses a simple linear regression analysis supported by SPSS. 17 program. From the simple linear regression analysis, it was obtained that the significance value is 0.105 (â‰¥0.05), which means that Ha is rejected and Ho is accepted. The correlation coefficient result is 0.167 that is on the range of 0.00-0.2, which means that the effect on news exposure of Lion Air on the internet towards the risk perception of students from Pekanbaru is very weak and may even be concluded as zero relation. In other words, results from this research show that there is no significant effect from the media exposure of Lion Air on the internet towards the perceived risk of students from Pekanbaru. Keywords: Media Exposure, Internet Media, Perceived Risk, Pekanbaru